2016
DOI: 10.1074/jbc.m116.718684
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid Is an Antagonist of Semen Amyloid Fibrils That Enhance HIV-1 Infection

Abstract: Recent in vitro studies have demonstrated that amyloid fibrils found in semen from healthy and HIV-infected men, as well as semen itself, can markedly enhance HIV infection rates. Semen fibrils are made up of multiple naturally occurring peptide fragments derived from semen. The best characterized of these fibrils are SEVI (semen-derived enhancer of viral infection), made up of residues 248 -286 of prostatic acidic phosphatase, and the SEM1 fibrils, made up of residues 86 -107 of semenogelin 1. A small molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…For example, based on its ability to abrogate SEVI-mediated enhancement of HIV-1 infection, the natural ingredient of green tea EGCG appears to be a promising supplement to antiretroviral microbicides [ 12 , 13 ]. A component of EGCG, gallic acid, is able to directly abrogate the viral enhancement of seminal fibrils and might be able to prevent HIV infection via sexual transmission [ 35 ]. Unfortunately, EGCG has poor solubility and poor oral bioavailability and easily undergoes oxidation in vivo, complicating its use in clinical trials [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, based on its ability to abrogate SEVI-mediated enhancement of HIV-1 infection, the natural ingredient of green tea EGCG appears to be a promising supplement to antiretroviral microbicides [ 12 , 13 ]. A component of EGCG, gallic acid, is able to directly abrogate the viral enhancement of seminal fibrils and might be able to prevent HIV infection via sexual transmission [ 35 ]. Unfortunately, EGCG has poor solubility and poor oral bioavailability and easily undergoes oxidation in vivo, complicating its use in clinical trials [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…BTA‐EG6 and its oligovalent derivatives prevented SEVI‐mediated enhancement of HIV infection. Gallic acid showed binding ability to SEVI amyloid fibrils and decreased semen‐mediated enhancement of HIV infection . Perturbation of surface electrostatics between cationic SEVI amyloids and HIV virions resulted in a decrease of HIV infectivity although the details on the physicochemical intermolecular interactions are unknown.…”
Section: Inhibition Of Sevi‐enhanced Hiv Viral Infectionmentioning
confidence: 99%
“…Gallic acid showed binding ability to SEVI amyloid fibrils and decreased semen-mediated enhancement of HIV infection. 48 Perturbation of surface electrostatics between cationic SEVI amyloids and HIV virions resulted in a decrease of HIV infectivity although the details on the physicochemical intermolecular interactions are unknown. Meanwhile, a D-enantiomeric peptide (RPRTRLHTHRNR), an inhibitor of Ab(1-42) amyloid formation, also attenuated SEVI amyloid-boosting infection of HIV.…”
Section: Development Of Agents To Suppress Hiv Interaction With Sevi mentioning
confidence: 99%
“…23 Interestingly, a recent study has found that a segment of EGCG, gallic acid ( Figure 2B), is a potent binder of SEVI fibrils and purportedly inhibits SEVI-mediated interactions with HIV and target cell surfaces by decreasing the positive charge potential on the surface of mature SEVI amyloids. 27 The small molecule surfen is another example of a SEVI-binding molecule that inhibits the interaction between SEVI and cellular and viral surfaces. 28 Prior to reports on the effects of EGCG and its derivatives as aggregation inhibitors of SEVI, we reported an initial study of a hexa(ethylene glycol) derivative of benzothiazole aniline (BTA-EG 6 , Figure 3B) as a small molecule inhibitor of SEVI-mediated HIV infection.…”
Section: Affect Hiv Transmissionmentioning
confidence: 99%